Valuing Florida Water Resources: Prices of Waterfront Properties - Tatiana Borisova; Xiang Bi; Tara Wade; Kurt Oehlbeck; Kelly Grogan (EDIS)
This 9-page fact sheet written by Tatiana Borisova, Xiang Bi, Tara Wade, and Kurt Oehlbeck and published by the UF/IFAS Food and Resource Economics Department explores the relationship between water quality and sale prices of waterfront properties, that is, the amenity value provided by water resources to waterfront communities. Being near to water to water generally increases the value of a residential property. However, poor water quality may decrease waterfront property prices. In other words, investments in restoring water quality can translate into increases in property value and tax collection. https://edis.ifas.ufl.edu/fe1062